2014
DOI: 10.7202/1025771ar
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Profile of Physical Education Teachers and Programs in Atlantic Canada

Abstract: The purpose of this research was to investigate the extent to which quality physical education is currently being taught in Atlantic Canada. We used survey methods to generate descriptive data indicating: (a) the backgrounds of those who teach physical education and (b) what is being taught in physical education. Our findings suggest physical education is taught by a group of mostly-white teachers with varying qualifications, interests, and experiences in teaching the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…One often-cited area of concern is the qualifications of teachers delivering PE, particularly at the elementary school level [ 10 – 12 ]. A PE specialist has been defined as a teacher who has majored or minored in PE in addition to completing a Bachelor of Education (BEd) degree, or who has received specialized and intense PE training during pre-service education [ 11 ], whereas a teacher with no specific PE training (apart from general PE courses required for all students in some BEd programs) is often considered a generalist.…”
Section: Introductionmentioning
confidence: 99%
“…One often-cited area of concern is the qualifications of teachers delivering PE, particularly at the elementary school level [ 10 – 12 ]. A PE specialist has been defined as a teacher who has majored or minored in PE in addition to completing a Bachelor of Education (BEd) degree, or who has received specialized and intense PE training during pre-service education [ 11 ], whereas a teacher with no specific PE training (apart from general PE courses required for all students in some BEd programs) is often considered a generalist.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an examination of related surveys conducted out with Scotland arguably confirmed Hardman and Marshall's (2000) concerns that too many studies focus in on a particular aspect of physical education: e.g. practitioners' attitudes towards educational reforms (Zach and Inglis, 2013); beliefs held in relation to their preparedness, enjoyment and confidence (Randall, Robinson, and Fletcher, 2014); attitudes concerning the teaching of physical activity and fitness (Guan, McBride and Xiang, 2005;Kulinna and Silverman, 2000); attitudes towards the use of information and communications technology (Thomas & Stratton, 2006); the examination of teachers' attitudes towards pupils with special educational needs (Meegan and MacPhail, 2008); as well as analyses of beliefs regarding the inclusion of pupils with additional support needs (Wang, Qi and Wang, 2015). Consequently, the instruments employed across those particular studies were tightly focused, with many developed, or amended, for the specific context and purpose of each investigation, limiting their usability for the setting and circumstances of the present study.…”
Section: Phase Onementioning
confidence: 77%
“…Generalists' lack of confidence to teach physical education is a common theme found in the literature (Decorby et al, 2005). In a previous study, Randall et al (2014) found that the majority of teachers focused on sport and games for the content of their physical education classes, despite the curriculum requiring otherwise. The teachers chose not to teach dance and gymnastics because of their low levels of preparedness, enjoyment and confidence (Randall et al, 2014).…”
Section: Discussionmentioning
confidence: 99%